Postqualitative Methods on Transcription: A Rhizomatic Approach - Xinqi He (International Journal of Qualitative Methods)
This paper echoes the worldview of post-qualitative study and aims to demonstrate an alternative way of doing transcription that addresses the rhizomatic feature of language. Conventional qualitative study based its foundation on representationalism which believes the transcript replicates the observed phenomena so that researchers can uncover the truth hidden under the transcript. However, post-qualitative studies on transcripts criticize the representationalist assumption as it fails to address the constantly changing nature of things. With the influence of French philosopher Deleuze and Guattari’s concept of the rhizome, post-qualitative studies use rhizoanalysis to highlight the connection and becoming of the phenomen. However, most of the rhizoanalysis on transcripts only engages with the changing nature of the content of things but not that of language. To understand how rhizomatic language can be addressed in a transcript, this study engages with a 7-s speech of an undergraduate student in a CLIL/EMI program in Japan and aims to address the potential in her language that precipitates the becoming of the language in the transcript. With this rhizomatic approach in transcription, this paper demonstrates the possibility of freeing language from normative constraints and open transcriptions and languages to be actualized into multiple forms that yet-to-come.